2018
DOI: 10.1016/j.actpsy.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Determining the end of a musical turn: Effects of tonal cues

Abstract: Successful duetting requires that musicians coordinate their performance with their partners. In the case of turn-taking in improvised performance they need to be able to predict their partner's turn-end in order to accurately time their own entries. Here we investigate the cues used for accurate turn-end prediction in musical improvisations, focusing on the role of tonal structure. In a response-time task, participants more accurately determined the endings of (tonal) jazz than (non-tonal) free improvisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Instead, such transitions may be coordinated by auditory cues, including both timing and tonal cues (see Hadley et al . [ 72 ], who found that tonal cues allow listeners to more accurately predict the end of a solo in standard jazz improvisation than free improvisation).…”
Section: Experiments 1: Predicting Visual Bouts Of Interaction From Momentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, such transitions may be coordinated by auditory cues, including both timing and tonal cues (see Hadley et al . [ 72 ], who found that tonal cues allow listeners to more accurately predict the end of a solo in standard jazz improvisation than free improvisation).…”
Section: Experiments 1: Predicting Visual Bouts Of Interaction From Momentioning
confidence: 99%
“…It seems in this case that this so-called 'trading solos', where performers alternate between playing together and each taking their turn in performing a solo (see [59] for details), does not put particular emphasis on coordinating performances via visual interactions near section boundaries. Instead, such transitions may be coordinated by auditory cues, including both timing and tonal cues (see Hadley et al [72], who found that tonal cues allow listeners to more accurately predict the end of a solo in standard jazz improvisation than free improvisation).…”
Section: Characterization Of Performers' Behavioursmentioning
confidence: 99%
“…Even if musicians were to decide to end the piece at the same time, it would still be difficult to do so. Contrary to other musical genres, such as straight‐ahead jazz, in which temporal and harmonic structures typically determine specific ending points (e.g., on the beat, or on a closing cadence), provide musicians with the support of a shared entrainment to a beat, or at the least, enable performers to rely on auditory imagery to form precise predictions about what is about to come next (Hadley, Sturt, Moran, & Pickering, 2018; Keller, 2008), in CFI there are no definite structures nor conventional patterns that point to specific ending points. As Alain Savouret—who taught free improvisation at Paris Conservatory for many years—nicely puts it: “If it's always difficult to start [an improvisation], it's even harder to finish it” (Savouret, 2010, p. 26).…”
Section: Introductionmentioning
confidence: 99%
“…The general dependence on memory may have implications for the reliability of global ratings collected following stimulus presentation. Memory is more robust for tonal music than atonal music (Halpern & Bartlett, 2010), which could have contributed to the differences observed between the pulsed and nonpulsed conditions, as the two styles also varied in terms of tonal content (Hadley, Sturt, Moran, & Pickering, 2018). With continuous ratings, memory demands are reduced as responses are made while the performances unfold, placing the two musical styles on a more level playing field in this respect.…”
Section: Experiments 2: Continuous Ratings Of Perceived Synchronymentioning
confidence: 99%